The impact of hepatitis C virus infection on early post-liver transplantation complications and early graft function in a single low-volume liver transplant center - Buivydienė, Arida; Basytė, Viktorija; Mašalaitė, Laura; Stanislovaitytė, Danguolė; Adomavičiūtė, Jurgita; Valantinas, Jonas (Acta medica Lituanica, 2015)
Background. End-stage liver disease associated with hepatitis C virus (HCV) infection has become one of the leading indications for liver transplantation. The effect of HCV infection on patients and long-term graft survival after orthotopic liver transplantation is well known. The aim of this study was to evaluate the impact of HCV infection on early post-liver transplantation complications and early graft function. Materials and methods. Between July 2005 and February 2015 60 cadaveric orthotopic liver transplantations were performed in 58 adult patients at the Vilnius University Hospital Santariškių Clinics. We retrospectively reviewed our low-volume liver transplant center experience. To evaluate the changes that occurred in HCV-positive and HCV-negative transplant recipients, the study population was divided into two groups according to their HCV status. Statistical analysis was performed using the Microsoft Excel and SPSS 20.0 program. Group differences and data reliability were determined by the Student’s t-test. Results. For 21 patients (35%) the indication for liver transplantation was end-stage liver disease due to HCV infection and for 39 patients (65%) there was another (non-HCV infection) indication. Overall, 29 patients (48%) have developed early biliary and/or vascular complications after transplantation: vascular complications were observed in 17 patients (28%) and biliary complications were observed in 12 patients (20%). Early graft function was good or fair in 52 patients (87%), primary dysfunction was observed in 8 (13%) patients. Conclusions. The incidence of early post-transplant complications and early graft dysfunction had no statistically significant difference according to the patient’s HCV status.
Keywords: hepatitis C; liver transplantation; early post-transplant complications; early graft function